O campo e o jogo: uma História do Estádio Castelão (1963-1991) - Souza, Pablo Eduardo da Rocha (2012)
The study aims to examine the planning, the construction and uses of the stadium Presidente Castelo Branco (Castelão), opened in Natal, capital of Rio Grande do Norte, in 1972. Used as main sources of documents printed newspapers A República, Tribuna do Norte e Diário de Natal; photographs of the 1960s, 1970s and 1980s and, finally, an interview with Moacyr Gomes da Costa, architect responsible for building the stadium Castelão. Seeks to understand the changes and continuities stemming from the construction of this stadium for football history and the city. Articulated in the text the inauguration of the stadium with the process of commodification and massification of football norte-rio-grandense, that occurred from the 1970s. Indicates the places where they practiced football in Natal before the construction of a stadium and analyzes the historical needs that led to the construction of a sports square. Discusses the transformation of football matches in shows profit, which now involve large economic interests. Investigates how political potiguares made use of football stadiums as a mechanism of legitimation and realize this debate with the performances of Djalma Maranhão and the Cortez Pereira, that at different times using this mechanism. Search elements that favored the popularization experienced by football potiguar from the 1970s, the role of the sports press this process and the emergence organized supporters